Evolution and vulnerability of the trade network structure of China’s petrochemical industry chain: Based on a comparative perspective between China and the US - Jianke, GUO; Jiaming, YANG; Fei, PENG; Hao, LUO; Liangshi, ZHAO (Zi yuan ke xue, 2025)
[Objective] The petrochemical industry is crucial for China’s economic stability. Investigating the structural evolution and vulnerability of China’s petrochemical industry chain trade network in the context of Sino-US strategic competition is of great significance for ensuring the industry’s secure and stable growth. [Methods] Complex network analysis was employed to analyze the structural evolution of China’s petrochemical industry chain trade network from 2007 to 2022. A Sino-US petrochemical industry chain trade network model was constructed to compare the influence of both countries. Scenario simulations based on the GDELT (Global Database of Events, Language, and Tone) bilateral relations data were conducted to evaluate the vulnerability of China’s petrochemical industry chain trade network. [Results] (1) China’s petrochemical industry chain made significant advancements in the field of petrochemical products, shifting from a raw material-dependent model to a product-export-oriented model. The trade partner structure expanded from an Asia-centered pattern to a global network, with continuous optimization of the industry chain trade network. However, structural vulnerabilities persisted in the basic chemical raw material network. (2) China and the United States shared highly overlapping trade partners in synthetic materials. The United States maintained its traditional advantages in petroleum and derived petroleum products, while China demonstrated stronger influence in the field of petrochemical products. (3) In terms of network vulnerability, China’s basic chemical raw material network showed relatively high vulnerability, particularly in the import segment, whereas the petroleum network exhibited diversification and stability. The organic chemical raw material network maintained stability with minor adjustments, and the petroleum products and synthetic material networks demonstrated low vulnerability. Under Sino-US strategic competition, decoupling from specific countries (regions) would lead to high vulnerability in China’s petroleum product imports and the import-export segments of basic chemical raw materials, but the impact on other segments of the industry chain remained relatively controllable. [Conclusion] China should deepen the “crude-to-chemicals” strategy, strengthen domestic energy security and international cooperation, and establish a risk assessment and early warning system to enhance the resilience and stability of the industry chain.